Pengaruh Produk Variety, Brand Image, Citarasa, Terhadap Keputusan Pembelian Mc’ Donalds (Studi Pada Mahasiswa Fakultas Ekonomi Dan Bisnis Unisma Malang) - Bahris Syamsi; Abdul Kodir Djaelani; Arini Fitria Mustapita (UNIVERSITAS ISLAM MALANG, 2023)
Abstract The purpose of this study is to determine the influence of variety products, brand image and taste on purchasing decisions. Using a sample of students of the Faculty of Economics and Business, Unisma Malang, this research is in November 2022 – January 2023. The results of this study showed that overall respondents chose strongly agreeing that Variety and Flavor Products had a significant influence on purchasing decisions on Mc'donalds. In addition to the Variety and Taste Product variables, the Brand Image variable has a low value so it does not significantly affect the purchasing decision of Mc'donalds. Keywords: Variety Product, Brand Image And Taste Of Purchasing Decisions